RASIONALISME ISLAM KLASIK DALAM PEMIKIRAN IBNU RUSYD - Nur Kholis (International Journal Ihya' 'Ulum al-Din, 2017)
This article is aimed at showing how the rationalism of Islamic thought has been well-ordered in the classical period. It also tries to describe Ibn Rushd’s philosophy with an explanation of the dialectic of thought and the background and impact of its influence. The dominance of orthodoxy in the classical era encouraged Ibn Rushd to think “antagonistically” about how to implement Islam rationally. The political situation in the Islamic world during the period of the Abbasid Daula also colored the dynamics of Islamic thought at that time; particularly the dialectic between the genuine currents of Islamic thought and Greek philosophy. In the philosophy of Ibn Rushd, some characteristics of Islamic rationalism can be found: (1) opposing the fatalism of belief and thought; (2) uniting the revelation (religion) and the reason (philosophy); (3) prioritizing the work of mind/takwil in solving all problems; (4) believing in the eternality of universal reason (al-‘aql al-fa’al).Artikel ini bertujuan menunjukkan betapa rasionalisme pemikiran Islam telah tertata kuat pada masa klasik. Artikel ini juga berupaya memaparkan filsafat Ibnu Rusyd yang disertai penjelasan mengenai dialektika pemikiran serta latar belakang dan dampak pengaruhnya. Dominasi pemikiran ortodoksi pada era klasik mendorong Ibnu Rusyd berpikir “antagonistik” tentang bagaimana berislam yang rasionalis. Situasi politik di dunia Islam pada masa Daulah Abbasiyah turut mewarnai dinamika pemikiran Islam saat itu; khususnya dialektika antara arus pemikiran Islam genuine dan filsafat Yunani. Dalam fisafat Ibnu Rusyd, dapat ditemukan beberapa karakteristik rasionalisme pemikiran Islam, yaitu: (1) menentang fatalisme keyakinan dan pemikiran; (2) menyatukan wahyu (agama) dan akal (filsafat); (3) mengutamakan kerja akal / takwil dalam menyelesaikan segala persoalan; (4) meyakini kekekalan akal universal (al-‘ql al-fa’al).